Analysis of Stress Concentration of Laminated Composite Plate With Circular Hole - Rameshwari Vivek Lalge; Dr. D. N. Kamble (International Journal of Innovations in Engineering Research and Technology, 2021)
Composite materials are finding a wide rangeof applications in structural design, especially for lightweightstructure that have stringent stiffness and strength requirements. They are attractive replacement for metallicmaterials for many structural applications. By finding efficient composite structure design that meets allrequirements of specific application. This is achieved by tailoring of material properties through selectivechoice of orientation, no. of stacking sequence of layers that make up composite material.Composites areused moreand more often for load carrying and safety structures in all kind of applications foe aviation andspace technology, for vehicles etc.Composite materials have been introduced progressively in automobiles,followingpolymer materials, a few of which have been used as matrices. It is interestingto examine therelative masses of different materials which are used in theconstruction of automobiles. Even thoughtherelative mass of polymer-based materials appears low, one needs to take intoaccount that the specific mass ofsteel is about 4 times greater than that of polymers.This explains the higher percentage in terms of volume forthe polymers.